Unemployment In Indonesia Due To Rising Inflation - Amin, Musdar M; Meini Rotinsulu, Clara Neltje (Yayasan Pendidikan Belajar Berdikari, 2023)
In Indonesia, inflation has climbed by 3.53% in the last year, bringing the country's inflation rate to 5.81% in October 2023. In Indonesia, the unemployment rate is 5.98%, with the number of jobless expected to reach 9.56 million by August 2023. Wage inflation, which occurs when there is a high demand for labour and wages are not offered rapidly enough, can have an influence on unemployment. Workers, on the other hand, will not accept low salaries if labour demand is low and unemployment is high. In Indonesia, inflationary pressures such as wage inflation and others can have an influence on unemployment.